Oxidation Behavior of Insecticide Azoxystrobin and its Voltammetric Determination Using Boron-doped Diamond Electrode - Šelešovská, Renáta; Herynková, Marie; Skopalova, Jana; Kelíšková, Pavlína; Janíková, Lenka; Cankar, Petr; Bednar, Petr; Chýlková, Jaromíra (Wiley-VCH, 2019)
Electrochemical oxidation of azoxystrobin, a systemic fungicide commonly used in agriculture to protect a wide variety of crops, was investigated using cyclic voltammetry with a boron-doped diamond electrode (BDDE) in aqueous buffer solutions. Two pH independent irreversible anodic current peaks controlled mostly by diffusion were observed in wide pH range (2 to 12) at potentials +1600mV and +2150mV vs. saturated silver-silver chloride electrode. Mechanism of the electrochemical oxidation was proposed and supported with high performance liquid chromatography/mass spectrometry analysis of azoxystrobin solutions electrolyzed on carbon fiber brush electrode. The main product of the first two-electron oxidation step was identified as methyl 2-(2-{[6-(2-cyanophenoxy)pyrimidin-4-yl]oxy}phenyl)-2-hydroxy-3-oxopropanoate. An analytical method for the determination of azoxystrobin in water samples and pesticide preparation by differential pulse voltammetry with BDDE was developed. The method provides a wide linear dynamic range (3.0x10(-7) to 2.0x10(-4)molL(-1)) with limit of detection 8x10(-8)molL(-1). Accuracy of the method was evaluated by the addition and recovery method with recoveries ranging from 96.0 to 105.8%. Interference study proved sufficient selectivity of the developed voltammetric method for the azoxystrobin determination in presence of azole fungicides as well as pesticides used to prevent the same crops.
Oxidační chování insekticidu azoxystrobinu a jeho voltametrické stanovení s využitím elektrody z borem dopovaného diamantu
Keywords: Pesticides; Azoxystrobine; Oxidation mechanism; Voltammetric determination; Boron-doped diamond electrode; Pesticidy; Azoxystrobin; Oxidační mechanismus; Voltametrické stanovení; elektroda z borem dopovaného diamantu